1987
DOI: 10.1037/0022-006x.55.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of psychotherapies for depressed elders.

Abstract: Ninety-one eldeis with a major depressive disorder (MOD) were treated for 16 to 20 sessions of behavioral, cognitive, or brief psychodynamic psychotherapy. Prior to treatment 20 of these subjects were assigned to a 6-week delayed treatment control condition. By the end of 6 weeks patients in the treatment conditions showed improvement, whereas controls did not. Overall, 52% of the treatment sample attained remission by termination; another 18% showed significant improvement. The remainder still met criteria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
262
2
9

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(280 citation statements)
references
References 16 publications
7
262
2
9
Order By: Relevance
“…Behavioural therapy ( Behavioural (8) Cognitive ( [11] Thompson (1987) Older adults community 67.07 (5.8) 67…”
Section: Resultsmentioning
confidence: 99%
“…Behavioural therapy ( Behavioural (8) Cognitive ( [11] Thompson (1987) Older adults community 67.07 (5.8) 67…”
Section: Resultsmentioning
confidence: 99%
“…This study also collected data from a pedometer as an objective measure of the client's physical activity. Several studies assessed self-rated engagement in terms of frequency and pleasantness of activities (Meeks et al, 2006(Meeks et al, , 2008Rokke et al, 1999;Thompson et al, 1987;Yon & Scogin, 2009) and frequency and duration of social and physical activity (Quijano et al, 2007). Only two studies included staff-reported activity participation and direct observation of activity participation and affective responses (Meeks et al, 2006(Meeks et al, , 2008.…”
Section: Dependent Measuresmentioning
confidence: 99%
“…They presented with major or minor depression, and comorbid anxiety was assessed in five studies (Acierno et al, 2012;Dozeman et al, 2011;Meeks et al, 2006;Thompson et al, 1987;Turner & Leach, 2009). Few studies included older adults with cognitive impairment (Snarski et al, 2011;Teri et al, 1997), chronic medical illness (Dozeman et al, 2011;Meeks et al, 2008;Quijano et al, 2007), chronic pain Meeks et al, 2006;Quijano et al, 2007), or diagnoses of psychiatric disorders such as schizophrenia (Snarski et al, 2011); thus, there is limited evidence for the effectiveness of behavioral activation with such individuals.…”
Section: Participant and Setting Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Beck, Hollon, Young, Bedrosian, and Budenz (1985) and Rush, Beck, Kovacs, and Hollon (1977) studies (data from these two studies were combined), the Luborsky andCrits-Christoph (1988) and the Thompson, Gallagher, and Breckenridge (1987) studies all yielded estimates of therapist effects equal to zero. Most of the other studies had modest therapist main effects (in the 5-10% of variance range).…”
Section: Therapist Effects In 10 Treatment Outcome Studiesmentioning
confidence: 99%